2022
DOI: 10.1038/s41467-022-34895-1
|View full text |Cite
|
Sign up to set email alerts
|

Defective activation and regulation of type I interferon immunity is associated with increasing COVID-19 severity

Abstract: Host immunity to infection with SARS-CoV-2 is highly variable, dictating diverse clinical outcomes ranging from asymptomatic to severe disease and death. We previously reported reduced type I interferon in severe COVID-19 patients preceded clinical worsening. Further studies identified genetic mutations in loci of the TLR3- or TLR7-dependent interferon-I pathways, or neutralizing interferon-I autoantibodies as risk factors for development of COVID-19 pneumonia. Here we show in patient cohorts with different se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
0
32
0
2
Order By: Relevance
“…One of the most important centres around the temporal association between immune markers and how these relate to disease trajectories and outcomes. For instance, recent studies have demonstrating that the timing when cytokines are measured may be critical in understanding the immune response in acute COVID-19 (58) understanding which markers are elevated at each stage of the disease and how this relates to COVID-19 outcomes is an important area for research in identifying different inflammatory phenotypes for targeted therapy in acute COVID-19. Approaches such as point-of-care testing for inflammatory markers and detailed characterisation of the immune response in COVID-19 may allow targeted treatment for different immune sub-phenotypes in both severe COVID-19 other critical illness states (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important centres around the temporal association between immune markers and how these relate to disease trajectories and outcomes. For instance, recent studies have demonstrating that the timing when cytokines are measured may be critical in understanding the immune response in acute COVID-19 (58) understanding which markers are elevated at each stage of the disease and how this relates to COVID-19 outcomes is an important area for research in identifying different inflammatory phenotypes for targeted therapy in acute COVID-19. Approaches such as point-of-care testing for inflammatory markers and detailed characterisation of the immune response in COVID-19 may allow targeted treatment for different immune sub-phenotypes in both severe COVID-19 other critical illness states (59).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important centres around the temporal association between immune markers and how these relate to disease trajectories and outcomes. For instance, recent studies have demonstrating that the timing when cytokines are measured may be critical in understanding the immune response in acute COVID-19 ( 58 ). Further understanding which markers are elevated at each stage of the disease and how this relates to COVID-19 outcomes is an important area for future research in identifying different inflammatory phenotypes for targeted therapy in acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we observed robust and sustained induction of all three types of interferons in patients with mild disease. Type I and type III interferons are the body's first-line defense against viral replication and spreading at the site of infection 38,39 , but their detection in the blood requires ultra-high sensitivity 40 . One previous study was unable to detect circulating IFNB and IFNG in COVID-19 patient sera using traditional ELISA 41 , and another study using the more sensitive SIMOA assay was able to detect IFNA in some patients but not in controls 27 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the current study is the first to report the detection of IFNW1 in circulation and the detection of all three interferon types in a single assay. In fact, the different detection sensitivities of different assays used in various studies might have contributed to discrepant findings regarding the relationship between interferons and disease severity 40 . Some studies found a less pronounced interferon alpha response in patients with severe disease than in those with mild disease 41,42 , another study reported persistently higher interferon alpha and lambda levels in patients with severe disease than in those with moderate disease 43 , and yet another study found no association between interferon alpha levels and disease severity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Опубликованные исследования выявили генетические мутации в локусах TLR3-или TLR7-зависимых путей интерферона-I с синтезом нейтрализующие аутоантитела к интерферону альфа [18]. Исходно высокий уровень, вероятно, снижает чувствительность рецепторов к интерферону и в результате отсутствие противовирусного действия [19] при тяжёлом течении COVID-19 [21], поскольку образование ловушек может спровоцировать иммунотромбоз, обусловленный активацией тромбоцитов и нейтрофилов [22].…”
Section: пациентыunclassified